2010
DOI: 10.4314/jasem.v13i1.55263
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of <i>Vigna Unguiculata</i> as a Phytoremediation Plant in the remediation of Crude Oil polluted soil for Cassava (<i>Manihot Esculenta</i>; Crantz) Cultivation

Abstract: ABSTRACT:The effectiveness of Vigna unguiculata as a phytoremediation plant in the remediation of crude oil polluted soil for cassava cultivation was carried out. Soil polluted with 50ml/kg of crude oil was phytoremediated with Vigna unguiculata alongside a control and double control. After 2 months of remediation, two cassava (Manihot esculenta) varieties (NR 8082 and TMS 30572) were planted. The level of remediation as well as the crop performance (growth and yield) and leaf chlorophyll content were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Despite this high population density, the extraordinary fertility of the Niger Delta soil has historically allowed the Ogoni people to make good living through subsistence farming and fishing. However, it is reported that their livelihood is being threatened (Tanee and Love, 2009).…”
Section: IVmentioning
confidence: 99%
“…Despite this high population density, the extraordinary fertility of the Niger Delta soil has historically allowed the Ogoni people to make good living through subsistence farming and fishing. However, it is reported that their livelihood is being threatened (Tanee and Love, 2009).…”
Section: IVmentioning
confidence: 99%
“…The potentials of similar vegetative components of plant have previously been reported by (Chen andLee,1997, Akonye andOnwudiwe, 2004). As a means of remediating soils polluted with petroleum derivatives or crude oil, soil amendments such as sawdust, peat, waste cotton and organic manures are added to soil (Tanee and Akonye, 2009). A soil amendment increases the ability of the soil matrix to supply biologically available water and nutrients to microorganisms that are capable of degrading the target compounds (Davis and Wilson, 2005).…”
Section: Growth Performance Of Cucumber (Cucumis Sativus L) In Spentmentioning
confidence: 99%
“…Maximum decrease (16.7%) was observed in 15 day old seedlings under 500 µM Zn stress (Figure 2). Earlier investigations showed that the heavy metals chromium, cadmium, manganese, lead and nickel [17] [23]- [25] reduces the leaf area; consequently total weight of the plant reduces. In this study, the reduced weight of the Zn-treated seedlings can be attributed to either a reduction in the number of cells or due to reduction in cell size.…”
Section: Statistical Analysis Of the Datamentioning
confidence: 99%
“…Hundreds of experiments have been conducted on this legume to understand its morphology, physiology, as well as to understand the effect of different stresses on this legume. However, only a scanty number of experiments have been carried out to study the Zn phytoextracting ability of V. unguiculata [17]. In the present study, an experiment was performed to evaluate the Zn phytoextracting ability of V. unguiculata under in vitro condition.…”
Section: Introductionmentioning
confidence: 99%